Seroprevalencia de Brucella spp. en cerdo de abasto en el Camal Municipal del Cantón Babahoyo - Veliz Morales, Génesis Geovanna (2023)
Porcine brucellosis is a disease caused by the bacteria brucella suis, which causes reproductive losses. The main objective of this research was to determine the seroprevalence of Brucella spp. in pigs for supply in the Municipal Camal of the Babahoyo Canton, with sample numbers of 267 pigs from different sectors that arrive at the slaughter center, there was the presence of a total of females (n=152), and a total of males (n=115) destined for sacrifice. The Rose Bengal (RB) Seroagglutination test was performed, sampling was demonstrated from the pigs before being slaughtered using the venipuncture technique in the jugular vein, blood samples were extracted and transferred to a refrigerator at a temperature of 4°. C to obtain the serum, in the Pathophysiology Laboratory of the Faculty of Agricultural Sciences of the Technical University of Babahoyo, to proceed with the rose bengal diagnostic technique, 0.30ul of the reagent (Rose Bengal) and 0.30ul were used. of serum on a glass plate to homogenize them, wait around 4 minutes making circular movements, after this the diagnosis is read directly with light, when diagnosing the results were 0% negative in Brucella spp, finding a low percentage of animals carriers of antibodies, in conclusion it was determined that brucellosis in the slaughterhouse was not diagnosed with positive cases, it is unusual with positive tests present in the samples studied in other slaughter centers.